Analogues of Picard sets for meromorphic functions with a deficient value - Kendall, Guy (2004)
Picard's theorem states that a non-constant function which is meromorphic in the complex plane C omits at most two values of the extended complex plane C*. A Picard set for a family of functions F is a subset E of the plane such that every transcendental f in F takes every value of C*, with at most two exceptions, infinitely often in C-E.